Long-term metformin treatment in adolescents with obesity and insulin resistance, results of an open label extension study - Lentferink, Y. E.; van der Aa, M. P.; van Mill, E. G. A. H.; Knibbe, C. A. J.; van der Vorst, M. M. J. (Nutrition & diabetes, 2018)
Background/Objectives Off-label metformin is nowadays frequently used for the treatment of obesity in adolescents. However, studies on long-term metformin treatment in adolescents with obesity are scarce. Therefore, an 18 month open label extension study following an 18 months randomized placebo-controlled trial (RCT) on the efficacy, safety, and tolerability of metformin in adolescents with obesity and insulin resistance was performed. Subjects/Methods After completion of the RCT, metformin was offered to all participants with a body mass index standard deviation score (BMI-sds) > 2.3 and Homeostasis Model Assessment for Insulin Resistance (HOMA-IR) ≥ 3.4. Endpoints were change in BMI and HOMA-IR. Results Overall, 31/42 participants completed the extension study (74% girls, median age 14.8 (11.6 – 17.9), BMI 31.2 (22.3 – 45.1), HOMA-IR 3.4 (0.2 – 8.8)). At start, 22/42 (52.4%) participants were eligible for metformin of which 13 (59.0%) agreed with treatment. In participants who continued metformin, an increase was observed in BMI (+2.2 (+0.2 to +9.0)) and HOMA-IR (+13.7 (+1.6 to +48.3)). In metformin naive participants, BMI stabilized after an initial decrease (+0.5 (−2.1 to +5.1)). For HOMA-IR, a decrease was observed (−1.1 (−4.6 to +1.4)). Conclusion While metformin treatment in metformin naive participants seems to result in an initial decrease in BMI and HOMA-IR, there is no evidence for sustained effect after prolonged use in adolescents. Limited compliance and/or insufficient dose may explain the differences in long-term effects between adolescents and adults.